P3.266 The Prevalence of HPV Genotypes in Patients with Genital Warts in Singapore - Will the HPV Vaccine Be Useful in This Population?. (13th July 2013) - Yew, Y; Sen, P; Chio, T; Koay, E; Chan, R
Abstract : Introduction: Worldwide, 90% of genital warts are caused by HPV types 6 and 11. A HPV vaccine covering HPV 6 and 11 is now available. To evaluate its potential benefits, we aim to characterise the prevalence of the HPV genotypes in genital warts in Singapore. Methods: We utilised a validated commercialised genotyping assay, the HybriBio HPV GenoArray test that is able to identify 21 HPV types including 5 low-risk types (6, 11, 42, 43, and 44). After a prior pilot study of ten patients, a total of 100 patients with genital warts and no prior treatment were recruited into this study. Scrapings from the warts were performed, stored in virus transport medium and DNA was then extracted for analysis. Demographics, sexual history and clinical findings were collected using a self-administered questionnaire. Results: There were 71 male and 29 female patients. The average age of the patients was 32.1 years. The majority (49%) were single and heterosexual. Approximately 50% of the patients had an average of more than five lifetime sexual partners. The majority (69%) had genital warts for the first time. HPV genotypes were characterised in 92% of the patients. Either HPV 6 and/or HPV 11 was detected in 87.0% of the patients. Thirty-four patients had high-risk HPV genotypes detected in their genital warts. Conclusion: A simple scraping methodology from genital warts followed by HPV typing (HybriBio HPV GenoArray test) has been shown to be reliable and effective in evaluating HPV genotypes in our population. The majority of the HPV genotypes characterised in all genital warts with readouts were either HPV 6 alone or HPV 11 alone or a combination of the two. This supports the use of a HPV vaccine targeting HPV 6 and 11 in the prevention of genital warts in Singapore.